Rodzina i jej rola w kształcowaniu życia religijnego według Pierwszego Synodu Diecezji Katowickiej - Jabłońska, Paulina (Studia Pastoralne, 2020)
The XX century is marked by great changes and transformations in every sphere of a human life. The supreme event which made a lot of changes in the Catholic Church is The Second Vatican Council. It performed a great renewal of a religiuos life. The Vatican II renewal influenced local churches in a great measure. In according, in Poland, we can see post-council revive synodal activity. The Church in Poland knows perfectly that the properly understood renewal of a religious life should begin in a family. That’s why the polish diocesan synods take family as a subject of their reflexion and renewal, especially I Synod of Katowice (1972-1975). The Article showes an achievement of the Synod in “a family and its role in a formation of a religious life”. The whole Article has been divided into two parts. The first reveals a family community as a source of religious life. The second one shows how the development of a religious life in a family is determined by the changes and renewal of a society. The Catholic Church should remember that small communities, especially families, are the basis of a parish renewal. A family is not only a basic organizational unit of the Church but also a reality in which the Church is formed.